2011
DOI: 10.1210/jc.2010-2858
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Copeptin in Preterm Infants: A Highly Sensitive Marker of Fetal and Neonatal Stress

Abstract: Copeptin is a highly sensitive marker of perinatal stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 12 publications
4
24
1
Order By: Relevance
“…There are many a priori reasons why copeptin might turn out to be a highly useful biomarker of birth asphyxia, and a number of previous observations point in this direction [4,5,21]. During birth, the HPA axis shows massive activation, which results in the release of AVP, and this response is further enhanced by various types of stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many a priori reasons why copeptin might turn out to be a highly useful biomarker of birth asphyxia, and a number of previous observations point in this direction [4,5,21]. During birth, the HPA axis shows massive activation, which results in the release of AVP, and this response is further enhanced by various types of stressors.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the underlying HPA-based mechanisms, copeptin levels in cord blood increase in different stress situations, such as infections and hypoxia, both in term and preterm pregnancies [4,5,21]. High copeptin levels at birth are related to acute adverse neonatal outcomes such as IVH [21]. …”
Section: Discussionmentioning
confidence: 99%
“…and Benzing et al found that compromised placental perfusion and chorioamnionitis were associated with significantly elevated cord copeptin levels in preterm infants born vaginally. (35) Copeptin is a biomarker of arginine vasopressin, which acts on multiple systems to increase blood pressure and water retention. Many studies suggest that copeptin levels might be useful in the early prediction of PE, as well as in the evaluation of the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, when plasma osmolality is higher, copeptin levels are also increased [25]. Some authors demonstrated that in adults, during a hypertonic saline infusion and thirsting, there is a rise of serum osmolality which results in the increase in serum copeptin concentration [26]. …”
Section: Discussionmentioning
confidence: 99%